Организация воздухообмена в жилых зданиях и энергосбережение - Маляренко, В. А.; Орлова, Н. А. (НТУ "ХПИ", 2004)
In article is made an analysis of the principal types system ventilation of the apartment houses, analysys its form factor, an account the influx-and-extract ventilation system subject to the using of a heat-exchange apparatus, the heaters, the filters, the estimate of a pay-back period and a air balance of the apartment houses under the condition the intermittent work system ventilation
Keywords: система вентиляции; вытяжная вентиляция; приточно-вытяжная система; поквартирная утилизация тепла